Developing new evaluation methods in systemic lupus erythematosus. (December 2015) - Spinelli, Francesca Romana; Ceccarelli, Fulvia; Alessadri, Cristiano; Scavalli, Antonio Sili; Conti, Fabrizio; Valesini, Guido
Monitoring systemic lupus erythematosus (SLE) requires comprehensive assessment of disease activity, comorbidities, chronic damage and patients' perspective of the disease. This narrative review summarizes the innovative and currently available tools to assess SLE patients in clinical research and routine practice setting focusing on what is new in the assessment of disease activity and damage, discussing composite indices and organ-specific scores; a separate section is dedicated to the imaging techniques useful to assess neuropsychiatric, musculoskeletal and renal involvement. SLE-related chronic damage and comorbid conditions contributing to patients' illness and long-term outcome are discussed. Finally, the impact of SLE on patients' quality of life is addressed focusing on self-reported questionnaires, adherence to treatment and work ability.